Inhibition of miR-146a Expression and Regulation of Endotoxin Tolerance by Rhesus Theta-Defensin-1 - Prasad Tongaonkar; Katie K. Trinh; André J. Ouellette; Michael E. Selsted (Mediators of Inflammation)
Theta- (θ-) defensins are pleiotropic host defense peptides with antimicrobial- and immune-modulating activities. Immune stimulation of cells with lipopolysaccharide (LPS, endotoxin) activates proinflammatory gene expression and cytokine secretion, both of which are attenuated by rhesus theta-defensin-1 (RTD-1) inhibition of NF-κB and MAP kinase pathways. Endotoxin tolerance is a condition that ensues when cells have an extended primary exposure to low levels of LPS, resulting in resistance to a subsequent LPS challenge. Recognition of LPS by Toll-like receptor-4 (TLR4) activates NF-κB, elevating levels of microRNA-146a (miR-146a), which targets IRAK1 and TRAF6 transcripts to reduce their protein levels and inhibits TLR signaling on secondary LPS stimulation. Here, we report that RTD-1 suppressed the expression of miR-146a and stabilized the IRAK1 protein in immune-stimulated, monocytic THP-1 cells. Cells that had primary exposure to LPS became endotoxin-tolerant, as evident from their failure to secrete TNF-α upon secondary endotoxin challenge. However, cells incubated with RTD-1 during the primary LPS stimulation secreted TNF-α after secondary LPS stimulation in an RTD-1 dose-dependent manner. Consistent with this, compared to the control treatment, cells treated with RTD-1 during primary LPS stimulation had increased NF-κB activity after secondary LPS stimulation. These results show that RTD-1 suppresses endotoxin tolerance by inhibiting the NF-κB pathway and demonstrates a novel inflammatory role for RTD-1 that is mediated by the downregulation of miR-146a during the innate immune response.